Effectiveness of Health Educational Program on Health Worker’s Knowledge to Integrated Management of Childhood Illness at Primary Health Care Centers in AL-Amara City - Mohamed Abbar Sharhan; Iqbal Ghanim Ali Ma’ala (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objectives : Evaluate the educational program’s effect on health-workers’ knowledge of the IMCI approach.Study design : A quasi-experimental design was implemented in the research to achieve the study goalsby using pre- and post-tests for one group of health workers This study was linked to the efficacy of anIntegrated Childhood Disease Management Health Education Program in primary health centers in Al-Amara Region. The research was conducted during the time October 13th 2019 to April 1st 2021.Data collection : A formal administrative approval to conduct this study was obtained from Misan Healthdirectorate and also obtained from each health workers through direct interviews .during the study period, atotal of (25) health workers served in IMCI units in primary health care centers and met the study requirementsand agreed to participate. Purposive study (Non-probability sample) were working in first health sector ofMisan health directorate .Conclusion :The study found that nursing at primary health care centers in Amara’s first health sector had amoderate level of knowledge about integrated management of childhood illness and there was no statisticalsignificant association between nursing characteristic and their general information.